2021
DOI: 10.1016/j.cell.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA vaccination induces functionally diverse antibodies to NTD, RBD, and S2

Abstract: In this study we profiled vaccine-induced polyclonal antibodies as well as plasmablast derived mAbs from individuals who received SARS-CoV-2 spike mRNA vaccine. Polyclonal antibody responses in vaccinees were robust and comparable to or exceeded those seen after natural infection. However, the ratio of binding to neutralizing antibodies after vaccination was greater than that after natural infection and, at the monoclonal level, we found that the majority of vaccine-induced antibodies did not have neutralizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
247
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 274 publications
(281 citation statements)
references
References 73 publications
31
247
3
Order By: Relevance
“…However, although B.1.1.7+E484K emerged several times independently, it does not seem to spread well -potentially due to the detrimental effect that the E484K mutation can have on binding affinity to human ACE2. 16 As expected and already shown by several publications, [28][29][30][31][32][33] neutralizing activity to B.1.351 was strongly reduced likely due to the three changes in RBD and extensive changes in the NTD. Interestingly, neutralizing activity was even more reduced for the local isolate of C.37 used in the current study which has more extensive changes in the NTD (Δ63-75 , Δ246-252) and the RBD (L452Q, E471Q, F490S) compared to the predominant C.37 variant (NTD: G75V, T76I, Δ246-252; RBD: L452Q, F490S).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, although B.1.1.7+E484K emerged several times independently, it does not seem to spread well -potentially due to the detrimental effect that the E484K mutation can have on binding affinity to human ACE2. 16 As expected and already shown by several publications, [28][29][30][31][32][33] neutralizing activity to B.1.351 was strongly reduced likely due to the three changes in RBD and extensive changes in the NTD. Interestingly, neutralizing activity was even more reduced for the local isolate of C.37 used in the current study which has more extensive changes in the NTD (Δ63-75 , Δ246-252) and the RBD (L452Q, E471Q, F490S) compared to the predominant C.37 variant (NTD: G75V, T76I, Δ246-252; RBD: L452Q, F490S).…”
Section: Discussionsupporting
confidence: 75%
“…Another interesting finding was that the reduction in binding activity to variant RBD and spike proteins was negligible. However, while neutralization activity is mostly dependent on only a few epitopes in the RBD and NTD, many more binding epitopes exist on the spike, 16 which may explain our findings. Interestingly, a recent study found even better correlation between binding activity and vaccine effectiveness than for neutralizing activity and vaccine effectiveness.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We previously reported on the isolation and characterization of plasmablast-derived antibodies from individuals who received the Pfizer/BioNTech mRNA SARS-CoV-2 vaccine BNT162b2 31 . We noted that the overall neutralizing antibody responses were directed towards both the RBD and NTD indicating co-dominance of these two spike domains.…”
Section: Neutralizing Antibody Pviv6-14 Binds a Lateral Cavity In The Ntdmentioning
confidence: 99%
“…We focus here on the early events of B cell activation after SARS-CoV-2 vaccination to structurally profile novel antibody epitopes. We previously identified a neutralizing monoclonal antibody (mAb), PVI.V6-14, derived from the plasmablast response mounted by a naïve study participant after two doses of mRNA vaccine whose heavy and light chains both contained no somatic hypermutation 31 . We determined its high-resolution structure in complex with the SARS-CoV-2 spike by single-particle electron cryomicroscopy (cryo-EM) and showed that it bound a lateral side of the N-terminal domain (NTD).…”
Section: Introductionmentioning
confidence: 99%